Genetic Diversity In Exotic Maize (Zea mays L.) Hybrids (Bangladesh Journal of Agricultural Research, 2013)
An experiment in alpha lattice design with three replication including 39 exotic maize hybrids was conducted at the Research farm of Regional Agricultural Research Station, BARI, Ishuardi, Pabna during Rabi season 2010-11 for analysis the genetic divergence in exotic maize hybrids. The genotypes were grouped in to seven clusters. Cluster VI comprised the maximum genotypes (13) indicating overall genetic similarity among them. The minimum genotype (1) was contained in the cluster III and V. The highest inter-cluster distance was observed between cluster V and III followed by cluster I and III and cluster III and VII suggesting wide diversity between them and the genotypes in these cluster could be used in hybridization program for obtaining a wide spectrum of variation among the segregates. The highest intra-cluster distance was observed in cluster VII and the cluster III and V were contained only one genotype and hence, their intra cluster distance was zero. The mean values of cluster IV recorded the highest yield per hectare (11.60 ton/ha) with medium plant height, days to maturity, days to 50% tasseling, silking and shelling percentage. Selection on the basis of plant aspect and ear aspect the genotypes of cluster III ranked first but plant height was high with medium seed size, medium yield, medium shelling percentage and also in late in case of maturity. The mean values of cluster V shown overall medium in case of yield and all yield contributing characters. Qualitative characters contribute maximum towards genetic divergence. Therefore, the genotypes from cluster III, V and VI could be utilized as source materials for getting desirable new recombinants with early maturity and higher yield. Bangladesh J. Agril. Res. 38(2): 335-341, June 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i2.15894